2020
DOI: 10.3389/fbioe.2020.00667
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Spatial Dynamics—Pharmacokinetic Model Explaining Poor Penetration of Anti-retroviral Drugs in Lymph Nodes

Abstract: Although combined anti-retroviral therapy (cART) suppresses plasma HIV viremia below the limit of detection in a majority of HIV patients, evidence is emerging that the distribution of the anti-retroviral drugs is heterogeneous in tissue. Clinical studies measuring antiretroviral drug concentrations in lymph nodes (LNs) revealed lower concentrations compared to peripheral blood levels suggesting poor drug penetration properties. Our current study is an attempt to understand this poor anti-retroviral drug penet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 48 publications
(77 reference statements)
2
13
0
Order By: Relevance
“…Furthermore, inflammation and fibrosis can alter the structure and size of the lymph node, disrupting normal pressure gradients and drug perfusion patterns throughout the tissue. 26,78,79 Jagarapu et al found an association between increased lymphoid lobule size and drug exclusion from the center of the lobule. 79 This is consistent with Jafarnejad et al's findings that lymphadenopathy during inflammation and/or viral infection can cause higher pressure in the lymph node and result in increased fluid flow back into blood vessels.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, inflammation and fibrosis can alter the structure and size of the lymph node, disrupting normal pressure gradients and drug perfusion patterns throughout the tissue. 26,78,79 Jagarapu et al found an association between increased lymphoid lobule size and drug exclusion from the center of the lobule. 79 This is consistent with Jafarnejad et al's findings that lymphadenopathy during inflammation and/or viral infection can cause higher pressure in the lymph node and result in increased fluid flow back into blood vessels.…”
Section: Reviewmentioning
confidence: 99%
“…26,78,79 Jagarapu et al found an association between increased lymphoid lobule size and drug exclusion from the center of the lobule. 79 This is consistent with Jafarnejad et al's findings that lymphadenopathy during inflammation and/or viral infection can cause higher pressure in the lymph node and result in increased fluid flow back into blood vessels. 26,80 Quantifying ARV concentrations and distribution in the lymph node Table 3 provides several examples of ARV concentrations quantified in lymph node tissue or isolated lymph node mononuclear cells (LNMCs).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…38 These lobules receive blood flow from specialized postcapillary venous channels known as high endothelial venules that facilitate the crossover from blood to LN parenchyma. 38 They are of particular interest due to the high density of cellular phenotypes that can be latently infected with HIV as well as previous identification of HIV persistence. Horiike et al utilized an NHP model that was chronically infected with SIV and suppressed on ART, to explore viral rebound after ART cessation.…”
Section: Lymph Nodesmentioning
confidence: 99%
“…40 LNs are pharmacologically unique since xenobiotics enter a lymphoid follicle (the primary point of entry into a LN lobule) through high endothelial venules vs. "traditional" blood flow as seen with other organs. 38 Like the CsfPR, a key measure of ART distribution into peripheral tissues is the tissue-to-plasma penetration ratio (TPR), which is the concentration of ART observed in a particular tissue normalized to that observed in the plasma at either a single matched moment in time or averaged over a defined time frame. A ratio of 1 indicates that the tissue exposure is equivalent to that of the blood.…”
Section: Lymph Nodesmentioning
confidence: 99%